Use of Peptides for the Management of Alzheimer’s Disease: Diagnosis and Inhibition - Baig, Mohammad H.; Ahmad, Khurshid; Rabbani, Gulam; Choi, Inho (Frontiers in Aging Neuroscience, 2018)
Alzheimer’s disease (AD) is a form of dementia and the most common progressive neurodegenerative disease. The targeting of amyloid-β (Aβ) aggregation is one of the most widely used strategies to manage AD. Efforts are being made globally to develop peptide-based compounds for early diagnosis and treatment of AD. Here, we briefly discuss the use of peptide-based compounds for the early diagnosis and treatment of AD and the use of peptide-based inhibitors at various Aβ aggregation checkpoints. Furthermore, we have briefly discussed the recent application of peptide based inhibitors against various AD targets including amyloid beta, BACE1, GAPDH, tyrosine phosphatase and potassium channel KV1.3.